Penerapan Bimbingan Kelompok Model Problem Based Learning untuk Meningkatkan Keterampilan Berpikir Kritis Siswa SMA - Masbahur Roziqi (Jurnal Psikoedukasi dan Konseling, 2022)
Abstract: This study aims to improve the critical thinking skills of class XII students through the group guidance model Problem Based Learning (PBL). There is also a scope which is limited to class XII students who take part in group guidance activities. The research method that the researchers used was classroom action research with two cycles. Each cycle consists of planning, action, observation, and reflection. The results of this study are that in the pre-cycle, students' critical thinking skills are still very low. In the pre-cycle the total score of the three students became 13. Then increased in the first cycle after receiving treatment, the total score became 29 points. In cycle II, critical thinking skills significantly increased the total score to 55 points. The conclusion of the action research that the researcher did was group guidance with the PBL model which was able to improve the students’ critical thinking skills.